2003
DOI: 10.1007/s10024-003-1115-0
|View full text |Cite
|
Sign up to set email alerts
|

Amniotic Sac Infection Syndrome Features Fetal Lung Neuroendocrine Cell Hyperfunction

Abstract: Epstein-Barr virus (EBV)-mediated lymphoid proliferations occur in patients who are immunocompromised and are reported following bone marrow or solid organ transplantation. Most post-transplant lymphoproliferative disorders (PTLD) are polymorphic in appearance; some are monomorphic and can resemble conventional malignant lymphomas. PTLD that resembles Hodgkin lymphoma has been reported infrequently. We herein report seven cases of PTLD that have large numbers of Reed-Sternberg-like (RS-like) cells and highligh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 41 publications
0
10
0
1
Order By: Relevance
“…Data on the treatment of HL-PTLD is even more scant and has been primarily restricted to case reports and case series totaling 39 patients [1021,38]. Chemotherapy has been commonly administered, although follow-up varied greatly across reports.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data on the treatment of HL-PTLD is even more scant and has been primarily restricted to case reports and case series totaling 39 patients [1021,38]. Chemotherapy has been commonly administered, although follow-up varied greatly across reports.…”
Section: Discussionmentioning
confidence: 99%
“…Disease outcomes and prognostication for patients who develop HL-PTLD are not well described. Most available data on the treatment of HL-PTLD have been reported in case reports and small series [922], and thus, there is minimal guidance when evaluating and treating this unique patient population. One registry study identified 60 patients with HL-PTLD in renal transplant recipients, all of whom were diagnosed prior to 2001 [6].…”
Section: Introductionmentioning
confidence: 99%
“…Случаи ПТЛПЗ, подобного лимфоме Ходжкина, встречаются очень редко, хотя и описаны [26][27][28]. Встречаемость данного состояния составляет 1,8-3,4 % от ПТЛПЗ у детей [29]. Наличие вариаций гистологической картины и клинических проявлений до сих пор вызывает дебаты, является ли эта патология формой лимфомы Ходжкина либо В-клеточным ПТЛПЗ.…”
Section: O N C O H E M a T O L O G Y 2 ' 2017 V O L 1unclassified
“…The recurrence rate of placental inflammation, either acute or chronic, is higher than that of hypoxic and thrombotic placental lesions [1]. The amniotic sac infection syndrome associated with acute chorioamnionitis and caused by the acute bacterial ascending infection is the most common single cause of perinatal mortality, particularly in the 2 nd trimester [2]. The role of chronic villitis in perinatal morbidity and mortality cannot be overemphasized.…”
Section: Introductionmentioning
confidence: 99%